Antibiotic susceptibility of isolated bacteria from cases of appendicitis in Sulaymaniyah city, Iraq - Hama, Nabaz Hamarashid; Arif, Huner Hiwa; Ameen, Sirwan Muhsin Muhammed (Sulaimani Journal for Pure and Applied Sciences, 2021)
Effective treatment of appendicitis requires the identification of the microorganism causing the condition, and the selection of antibiotics the bacterial pathogens are susceptible to. Isolation of 165 potential pathogenic bacteria took place from 50 patients suffering from acute appendicitis, and both the conventional and Vitek 2 compact automated systems were used for identification. In vitro testing of bacterial isolates were used to examine the susceptibility and minimum inhibitory concentrations (MICs) of infectious agents to various antibiotics. Escherichia coli (27.27%) was the most prevalent microorganism, followed by Staphylococcus aureus and anaerobic Bacteroides fragilis (7.8%). For E. coli, its susceptibility to Ciprofloxacin Gentamicin, Imipenem, Amoxicillin, and Amoxicillin/Clavulanate acid amounted to 72%, 100%, 100%, 80%, and 76%, respectively. For B. fragilis, its susceptibility to Imipenem, Metronidazole, Cefoxitin, Amoxicillin-Clavulanate, and Piperacillin Tazobactam amounted to 100%, 100%, 100%, 60%, and 80%, respectively. Various bacterial isolates, including E. coli, B. fragilis, and S. aureus were identified as the most prevalent organisms isolated from the sample of acute appendicitis patients. For clinical use, combined Ciprofloxacin and Metronidazole administration as prophylactic antibiotics or treatments is recommended to treat acute appendicitis.
Keywords: Acute appendicitis; Appendectomy; Bacteria; Antibiotics; Sulaimani